Expression profile of microRNA-146a along HPV-induced multistep carcinogenesis: a study in HPV16 transgenic mice - Rita Araújo (2018)
Purpose Persistent human papillomavirus (HPV) infection is associated with the development of certain types of cancer and the dysregulation of microRNAs has been implicated in HPV-associated carcinogenesis. This is the case of microRNA-146a (miR-146a), which is thought to regulate tumor-associated inflammation. We sought to investigate the expression levels of miR-146a during HPV16-mediated carcinogenesis using skin samples from K14-HPV16 transgenic mice which develop the consecutive phases of the carcinogenesis process. Methods Female transgenic (HPV+/-) and wild-type (HPV-/-) mice were sacrificed at 24-26 weeks-old or 28-30 weeks-old. Chest and ear skin samples from HPV+/- and HPV-/- mice were histologically classified and used for microRNA extraction and quantification by qPCR. Results Chest skin samples from 24 to 26 weeks-old HPV+/- mice presented diffuse epidermal hyperplasia and only 22.5% showed multifocal dysplasia, while at 28-30 weeks-old all (100.0%) HPV+/- animals showed epidermal dysplasia. All HPV+/- ear skin samples showed carcinoma in situ (CIS). MiR-146a expression levels were higher in HPV+/- compared to HPV-/- mice (p = 0.006). There was also an increase in miR-146a expression in dysplastic skin lesions compared with hyperplasic lesions (p = 0.011). Samples showing CIS had a significant decrease in miR-146a expression when compared to samples showing epidermal hyperplasia (p = 0.018) and epidermal dysplasia (p = 0.009). Conclusions These results suggest that HPV16 induces the overexpression of miR-146a in the initial stages of carcinogenesis (hyperplasia and dysplasia), whereas decreases its expression at later stages (CIS). Taken together, these data implicate and suggest different roles of miR-146a in HPV-mediated carcinogenesis.